Correction: Long-term C. elegans immobilization enables high resolution developmental studies in vivo. Issue 12 (29th May 2018) - Berger, Simon; Lattmann, Evelyn; Aegerter-Wilmsen, Tinri; Hengartner, Michael; Hajnal, Alex; deMello, Andrew; Casadevall i Solvas, Xavier
Abstract : Correction for 'Long-term C. elegans immobilization enables high resolution developmental studies in vivo ' by Simon Berger et al., Lab Chip, 2018, 18, 1359–1368.